Cobalt Single‐Atom Reverse Hydrogen Spillover for Efficient Electrochemical Water Dissociation and Dechlorination - Zheng, Qian; Xu, Hengyue; Yao, Yancai; Dai, Jie; Wang, Jiaxian; Hou, Wei; Zhao, Long; Zou, Xingyue; Zhan, Guangming; Wang, Ruizhao; Wang, Kaiyuan; Zhang, Lizhi (Angewandte Chemie International Edition, 2024)
Efficient water dissociation to atomic hydrogen (H*) with restrained recombination of H* is crucial for improving the H* utilization for electrochemical dechlorination, but is currently limited by the lack of feasible electrodes. Herein, we developed a monolithic single‐atom electrode with Co single atoms anchored on the inherent oxide layer of titanium foam (Co1−TiOx/Ti), which can efficiently dissociate water into H* and simultaneously inhibit the recombination of H*, by taking advantage of the single‐atom reverse hydrogen spillover effect. Experimental and theoretical calculations demonstrated that H* could be rapidly generated on the oxide layer of titanium foam, and then overflowed to the adjacent Co single atom for the reductive dechlorination. Using chloramphenicol as a proof‐of‐concept verification, the resulting Co1−TiOx/Ti monolithic electrode exhibited an unprecedented performance with almost 100 % dechlorination at −1.0 V, far superior to that of traditional indirect reduction‐driven commercial Pd/C (52 %) and direct reduction‐driven Co1−N−C (44 %). Moreover, its dechlorination rate constant of 1.64 h−1 was 4.3 and 8.6 times more active than those of Pd/C (0.38 h−1) and Co1−N−C (0.19 h−1), respectively. Our research sheds light on the rational design of hydrogen spillover‐related electrocatalysts to simultaneously improve the H* generation, transfer, and utilization for environmental and energy applications. The immobilization of Co single atoms on the surface oxide layer of titanium foam favors the rapid diffusion of generated atomic hydrogen to adjacent Co single atoms through the reverse hydrogen spillover effect for more efficient electrochemical dechlorination of chloramphenicol, offering a promising atomic hydrogen utilization strategy for environmental and energy applications.